2005
DOI: 10.1590/s0104-07072005000200002
|View full text |Cite
|
Sign up to set email alerts
|

Educación para el autocuidado de pacientes diabéticas embarazadas

Abstract: La investigación objetiva a comparar la educación que poseen las diabéticas embarazadas antes y después de recibir el Programa Educativo para el Autocuidado de la Diabetes Mellitus en sus factores: conocimientos teóricos, capacitación práctica, y actitudes frente a la Diabetes. Asimismo se determinó la relación existente entre las variables: características clínicas, socioeconómicas, y nivel de instrucción de las embarazadas con los resultados de la medición de los conocimientos de dicho Programa. El diseño fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
1
0
2
Order By: Relevance
“…87 It is well established in Venezuela that population-based education of people with T2D is critical to achieve their active and effective participation in the control and treatment of their disease. 89,90 Previously, the IDPMS found that diabetes education was associated with significantly improved glycemic control, greater use of insulin, lower rates of several chronic complications, and higher rates of employment. 91 In Venezuela, patients with T2D treated with insulin receive more frequently diabetes education interventions (63.7%) than those with only OGLD (56.6%).…”
Section: Challenges and Recommendations For Successful Management Of mentioning
confidence: 99%
“…87 It is well established in Venezuela that population-based education of people with T2D is critical to achieve their active and effective participation in the control and treatment of their disease. 89,90 Previously, the IDPMS found that diabetes education was associated with significantly improved glycemic control, greater use of insulin, lower rates of several chronic complications, and higher rates of employment. 91 In Venezuela, patients with T2D treated with insulin receive more frequently diabetes education interventions (63.7%) than those with only OGLD (56.6%).…”
Section: Challenges and Recommendations For Successful Management Of mentioning
confidence: 99%
“…Esta crisis de los últimos veinte años ha disminuido drásticamente el poder adquisitivo de la población, conllevando a un descenso en él numero de calorías per capita, así como en el consumo de carnes rojas, pollo, pescado, legumbres, hortalizas y frutas, según lo demuestran estudios realizados a un antes de 1987. 2,3 Este hecho, indiscutiblemente repercute en las posibilidades de cumplimiento de un plan alimentario conveniente por parte de los diabéticos.…”
Section: El Escenario De La Investigaciónunclassified
“…Nesse sentido, Souza e Lima (2007) referem sobre a possibilidade de "cura" a partir da criação de novas normas de vida decorrentes do acometimento por determinada doença e então, independente da caracterírstica da doença instalada a pessoa passar a se sentir saudável. Assim enquanto profissionais devemos analisar se nossas práticas tem incorporado o papel de incentivar as pessoas a buscarem esse estado de saúde que transcende os limites impostos pela doença Vários autores (TORAL;SLATER, 2007;FRANCIONI;COELHO, 2004;GUERRA, 2005) colocam que a base para o alcance de um estado de emancipação frente a uma doença é o conhecimento acerca da mesma. Assim os participantes da pesquisa confirmam essas inferências ao comunicarem que o conhecimento relacionado ao diabetes e seu tratamento também foi parte das conquistas alcançadas.…”
Section: (Pedro)unclassified